Imaging analysis technique for assessing orange maturity - Elmetwalli, A. H.; Salah, Sh. (2015)
The objective of the present study was to develop a computer vision and image analysis program to serve as a simple and suitable technique for external fruit inspection and for predicting orange fruits maturity through the image analysis technique. The ENVI software package was utilized for image processing and analysis. The study also investigated the effectiveness of some color bands including RIG ratio, average of RGB bands (intensity) and VARI indices for predicting biochemical properties including chlorophyll a and b, carotenoids, acidity, pH, tss, and tsslacidity. Absorbance of the extracts was read by a spectrophotometer at specific wavelengths of 470, 645 and 662 nm to determine chlorophylls and carotenoids concentrations. The results revealed that the computer vision and image analysis program could be used to differentiate orange maturity stages. The results also showed that there is a strong response between both chlorophyll and carotenoids of orange fruits and the band ratios used in this research. RIG band ratio, average of RGB pnd VARI indices showed sensitive band, ratios to different orange biochemical properties. Keywords: image analysis, computer vision, orange, carotenoids, RGB, band ratios.
Includes references.
Summary in Arabic.
1
Keywords: Plants -- Analysis; Image analysis -- Data processing; Phenotype